2016
DOI: 10.11604/pamj.2016.24.77.8916
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with tungiasis in Mayuge district, Eastern Uganda

Abstract: IntroductionTungiasis is an endemic but neglected health problem in Uganda especially in resource poor communities. It is largely affecting rural communities in the Eastern, West Nile and Central regions. This study assessed prevalence and risk factors associated with tungiasis in Mayuge district, Eastern Uganda.MethodsThis was a cross sectional study that used a semi-structured questionnaire and observational checklist to collect quantitative data from 422 households in 12 villages. Prevalence of tungiasis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
(25 reference statements)
4
27
2
Order By: Relevance
“…In contrast, other studies conducted in east Africa have reported a large burden of tungiasis. A household survey conducted in rural eastern Uganda reported that 22.5% of respondents were affected by tungiasis at the time of data collection and that 41.5% had been affected in the preceding month[ 11 ]. Similarly, a community based study in western Tanzania reported a prevalence of 42.5%[ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies conducted in east Africa have reported a large burden of tungiasis. A household survey conducted in rural eastern Uganda reported that 22.5% of respondents were affected by tungiasis at the time of data collection and that 41.5% had been affected in the preceding month[ 11 ]. Similarly, a community based study in western Tanzania reported a prevalence of 42.5%[ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tetanus infection in Uganda is still common with a two fold increase in the number of female cases aged 5 or more old were observed from 755 in 2011 to 1665 in 2014; similarly the number of males aged 5 years or older increased from 1007 to 1311 in the same period [11], and wounds due to trauma have been reported, especially among farmers [14]. Road traffic injuries are also common [15–16], as are Jigger infestations (Tungiasis) [17]. Therefore, the risk of current or recently healed wounds and jigger infestations among SMC clients remains a public health challenge which needs to be addressed with better tetanus toxoid vaccination coverage and wound care to minimize the risk of tetanus [18]…”
Section: Discussionmentioning
confidence: 99%
“…8 Within the African subcontinent while endemic Tungiasis has been reported from neighbouring countries of Uganda and Tanzania there are no reports from the eastern parts of DRC although there is anecdotal evidence that it is well known among the local population. 9,10 Troops and their accompanying medical personnel, travelling to foreign or unknown territory, should familiarize themselves with the local endemic diseases. Tungiasis is an ectoparasitosis and the flea is found in the dry sandy soil of endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Tungiasis however is an import endemic disease in the region, as seen by recent reports of high endemic load in geographically close areas to eastern DRC like Kenya, Uganda and Tanzania. 4,9,10…”
Section: Discussionmentioning
confidence: 99%